44 Swindon heart attack program to evaluate and improve timing of angiography in nstemi (shape-it nstemi). (6th June 2022) - Hyde, Tom; Taylor, Jon; Marquiss, Lucy; Kopanska, Agnieszka; Cobb, Tessa; Plumb, Andrea; Kelland, Emmakate; Rees, Monica; Taylor, Stephanie; Pidduck, Susanne; Darmody, Teresa; Darby, Karen; et al.
Abstract : Aim: To improve NSTEMI care; with a particular focus on the timing of angiography in NSTEMI and same day discharge after angiography and follow on percutaneous coronary intervention (PCI).Setting: Single site non-surgical centre in the NHS, with a national target for 75% of NSTEMI patients to have angiography within 72 hours of admission. Methods: In August 2020 we invited a change expert to facilitate a session. Stakeholders included: Nurses- ACS/ACU/Cardiology Ward/Cath Lab/Rehab/MINAP audit/Matron; Head of Service; Site managers; Radiographers; Cardiac physiologists; Emergency Physicians; Paramedics; Cardiologists and our local pathway manager. The session focussed on heart attack care and set realistic goals. The patient pathway, current model of care and future directions were discussed, and an improvement plan was made. The goals included Improving patient experience ≥ 75% of angiography within 72 hours of admission for NSTEMI Increased same day discharge (golden patient) Direct admission to a free bed on the Acute Cardiac Unit (ACU) for high risk NSTEMI from the community via the ambulance serviceThe key steps to achieving change were Smart listing –cases were labelled NSTEMI or NSTEMI GP (golden patient) on the ordering system – started in April 2021 Buy in from operators for a NSTEMI patient on the list each morning ahead of elective work Recovering PCI cases in the general cardiology ward NSTEMI patient information, a new leaflet given to patients by the rehab team A half an hour biweekly meeting was held on Teams facilitated by our pathway manager. Progress was tracked, these meetings also generated ideas. Results: The project started in September 2020. The percentage of NSTEMI patients undergoing angiography increased steadily from a baseline of 60% to the most recent figure of 93%. In the six months following the introduction of smart listing, the same day discharge rate, or 'Golden Index' was 41% up from 27% in the preceding 6 months. On a base of 400 MINAP verified NSTEMI patients that is a saving of 56 hospital bed days.A patient satisfaction survey following discharge of 15 randomly selected recent patients showed an 87% understanding rate of their diagnosis and treatment. Conclusion: A local approach to pathway management for NSTEMI, involving stakeholders was successful in improving care, preserving income, freeing up hospital beds and will hopefully continue to deliver further benefits. Conflict of Interest: None To Declare